2014
DOI: 10.1007/s00261-014-0134-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of myometrial invasion in endometrial cancer: comparison of diffusion-weighted magnetic resonance and intraoperative frozen sections

Abstract: In assessing the depth of myometrial invasion, ADC maps show the same accuracy as intraoperative histological studies in endometrial cancers. They also allow for a more precise assessment than conventional MRI sequences. Frozen-section analysis can be avoided if the preoperative MRI study includes DWI sequences and ADC maps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 17 publications
2
36
0
Order By: Relevance
“…Several techniques can be used for the preoperative assessment disease invasion. Magnetic resonance imaging (MRI) has a sensitivity of 57.9% in determining deep myometrial invasion, and an accuracy of 80.4% (Gallego et al, 2014). In another study, sensitivity, specificity, NPV, PPV and accuracy for diagnosing deep MI were 69.0%, 93.1%, 91.3%, 74.1%, and 87.8%, respectively, for MRI (Hahn et al, 2013).…”
Section: 6353 Risk Factors For Lymph Node Metastases With Endometriamentioning
confidence: 91%
See 1 more Smart Citation
“…Several techniques can be used for the preoperative assessment disease invasion. Magnetic resonance imaging (MRI) has a sensitivity of 57.9% in determining deep myometrial invasion, and an accuracy of 80.4% (Gallego et al, 2014). In another study, sensitivity, specificity, NPV, PPV and accuracy for diagnosing deep MI were 69.0%, 93.1%, 91.3%, 74.1%, and 87.8%, respectively, for MRI (Hahn et al, 2013).…”
Section: 6353 Risk Factors For Lymph Node Metastases With Endometriamentioning
confidence: 91%
“…Sensitivity, specificity, NPV, PPV and accuracy for diagnosing deep MI were 85.7%, 96.8%, 95.8%, 88.9%, and 94.3% for intraoperative frozen section (IFS) (Hahn et al, 2013). In another study the accuracy, sensitivity, specificity, PPV, and NPV for detecting deep invasion of the myometrium were 90.2%, 73.7%, 100%, 100%, and 86.5%, respectively (Gallego et al, 2014).…”
Section: 6353 Risk Factors For Lymph Node Metastases With Endometriamentioning
confidence: 95%
“…21,24 However, some physicians suggest that MRI with diffusion-weighted imaging has the same accuracy as intraoperative FSs. 22 Furthermore, none of the patients identified as low-risk by both MRI and FSs had pelvic or para-aortic lymph node metastasis in the final pathology. 23 The evaluation of the tumor grade by FSs has been reported to have a sensitivity of 40% to 98%, a specificity of 53% to 98%, and an accuracy of 83% to 89%.…”
Section: Discussionmentioning
confidence: 91%
“…In the study by Hori et al, 22 2 different observers prospectively estimated the myometrial invasion using DW-MRI in a total of 71 patients, showing a good accuracy (87% and 92%), sensitivity (95% and 84%), and specificity (85% and 94%). Gallego et al, 20 in a comparative study, reported an accuracy, sensitivity, and specificity of 90.2%, 77.8%, and 97% respectively, for DW-MRI. Our data are in line with the meta-analyses by Andreano et al 28 who reported a sensitivity and a specificity of 86%, considering 9 studies with a total of 442 patients.…”
Section: Discussionmentioning
confidence: 95%